Braquiópodes (Rhynchonelliformea, Bouchardioidea) neógenos da bacia de Pelotas (RS) e seu significado paleoambiental - Guimaraes Simoes, Marcello; da Silva, Suzana Aparecida Matos; Coelho Rodrigues, Sabrina; Coimbra, Joao Carlos (My University, 2008)
The occurrence of brachiopods in Cenozoic rocks of the Pelotas Basin is known since 1862. In spite of that, detailed systematic and taphonomic studies are still missing. Investigations made a half century ago, have suggested that these brachiopods could belong to Bouchardia cf. zitteli, a species found in the San Julian Formation, Late Oligocene, Argentina. Our data suggest that those brachiopods may resemble Bouchardia transplatina. In the Uruguayan portion of the Pelotas Basin B. transplatina is known in rocks of the Camacho Formation, Miocene. In addition, small recrystallized shells of brachiopods were also recovered from three Petrobras boreholes (2PJ-1-RS, 2PN-1-RS, and 2GA-1-RS) from the Pelotas Basin. Brachiopods come from the interval of 130 to 150 meters within the Miocene Henryhowella evax Zone. Despite the degree of taphonomic modiication of those brachiopod shells they indubitably belong to Bouchardia sp. This is noteworthy for various reasons: 1- Bouchardia is a brachiopod with warm water afinities. Presently, extant members of this genus are unknown in latitudes up to 34[degree]S, with the main records at 23[degree]S. 2- Although occurring in depths down to 200 meters, the living member (Bouchardia rosea) of this genus is most abundant in shallow platformal, nutrient-rich waters. 3- The occurrence of Bouchardia in the Miocene of the Pelotas Basin indicates that, at least to the interval of Henryhowella evax Zone, warm waters of the Brazilian currents prevail. This interpretation is in strong accordance with other paleoeoceanographic and paleoclimatic data offered by various groups of co-occurring microfossils, such as ostracodes and foraminifers.

A ocorrência de braquiópodes no Neógeno da Bacia de Pelotas é conhecida desde 1862. A despeito disso, porém, estudos detalhados de sistemática e tafonomia ainda não existem. Investigações conduzidas meio século atrás indicaram que os braquiópodes poderiam ser atribuídos à espécie Bouchardia cf. zitteli, comum à Formação San Julian, Oligoceno Superior, Argentina. A revisão realizada indica, contudo, que a espécie presente é Bouchardia transplatina. Na porção uruguaia da Bacia de Pelotas, B. transplatina é conhecida na Formação Camacho, Mioceno. Em adição, pequenas conchas de braquiópodes foram recuperadas também de material de calha, de poços Petrobras (2PJ-1-RS, 2PN-1-RS e 2GA-1-RS), na porção continental da Bacia de Pelotas. Esses braquiópodes provêm de intervalo estratigráfico (130 a 150 metros) correspondente à Zona Henryhowella evax (Mioceno). A despeito do alto grau de dissolução das conchas, essas podem ser atribuídas, sem dúvida, a Bouchardia sp. Os dados acima são relevantes, pois: 1- Bouchardia possui afinidades com águas quentes (tropicais/subtropicais). Presentemente, formas viventes desse gênero habitam águas em latitudes de até 34°S, mas a maior abundância está em torno de 23°S; 2- embora ocorram em profundidades superiores a 200 metros, Bouchardia rosea (espécie vivente) é mais abundante em águas plataformais rasas, ricas em nutrientes; 3- a presença de Bouchardia, no Mioceno da Bacia de Pelotas indica que, pelo menos no intervalo da Zona Henryhowella evax, condições de águas quentes relacionadas à Corrente do Brasil, prevaleceram. Essa interpretação está de acordo com dados paleoeoceanográficos e paleoclimáticos, fornecidos por ostracodes e foraminíferos que co-ocorrem com os braquiópodes estudados.
Neogene brachiopods (Rhynchonelliformea, Bouchardioidea) from the Pelotas Basin (RS) and their paleoenvironmental significance